2014
DOI: 10.3390/nu6052059
|View full text |Cite
|
Sign up to set email alerts
|

Purification of Alaskan Walleye Pollock (Gadus chalcogrammus) and New Zealand Hoki (Macruronus novaezelandiae) Liver Oil Using Short Path Distillation

Abstract: The beneficial health effects of a diet rich in n-3 long chain polyunsaturated fatty acids (n-3 LC-PUFA) have been extensively researched in recent years. Marine oils are an important dietary source of n-3 LC-PUFA, being especially rich in two of the most important fatty acids of this class, EPA (eicosapentaenoic acid; 20:5n-3) and DHA (docosahexaenoic acid; 22:6n-3). Oils rich in n-3 LC-PUFA are prone to oxidation that leads to loss of product quality. Alaskan pollock (Gadus chalcogrammus Pallas, 1814) and Ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 31 publications
2
12
0
1
Order By: Relevance
“…Typically, volatile components, mainly including aldehydes and ketons in fish oils may be mainly originated from the microbial spoilage and autoxidation of proteins, amino acid, and lipids. In most cases, these substances are not desirable for human consumption . Furthermore, n‐3 FAs in fish oils are exceptionally susceptible to oxidation, and the breakdown of n‐3 chain during oxidation process causes nutritional loss and detrimental sensory, with an unacceptable rancidity and fishy odor .…”
Section: Introductionmentioning
confidence: 99%
“…Typically, volatile components, mainly including aldehydes and ketons in fish oils may be mainly originated from the microbial spoilage and autoxidation of proteins, amino acid, and lipids. In most cases, these substances are not desirable for human consumption . Furthermore, n‐3 FAs in fish oils are exceptionally susceptible to oxidation, and the breakdown of n‐3 chain during oxidation process causes nutritional loss and detrimental sensory, with an unacceptable rancidity and fishy odor .…”
Section: Introductionmentioning
confidence: 99%
“…Fregolente, Pinto, Wolf-Maciel, & Filho, 2010) or camellia oil (Zheng, Xu, Wang, Qin, Ning, Wang, et al, 2014) have been also reported. Processing of marine oils by SPD to remove pollutants and oxidation products has been reported (Oliveira & Miller, 2014;Oterhals & Berntssen, 2010), however, the studies focused on PUFA purification mainly obtained the PUFA concentrate in FFA or EE form (Breivik, Haraldsson, & Kristinsson, 1997;Kahveci & Xu, 2011;Rossi, Grosso, Pramparo, & Nepote, 2012;Zhang, Liu, & Liu, 2013). Other studies have used SPD to remove ethyl esters subsequently to ethanolysis in order to obtain an acylglycerol product (mainly DAG) rich in DHA and EPA (Lyberg & Adlercreutz, 2008;Martín Valverde, González Moreno, Rodríguez Quevedo, Hita Peña, Jiménez Callejón, Esteban Cerdán, et al, 2012;Valverde, Moreno, Callejón, Cerdán, & Medina, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Mice in Group G6 were given the same EVSO as in G4 containing 120mg/g EPA+DHA but treated with heat at 190C for 5 minutes to simulate vacuum molecular distillation. [ 28 ] Mice in Group G7 were given EVSO as in G4 but the EVSO was hydrolyzed with base and re-esterified with glycerol/acid as done in the standard fractional distillation step [ 29 ] often carried out for producing EPA/DHA concentrated fish oils. Finally, the mice in Group G8 were given EVSO as in G4 but the EVSO had been oxidized (by air bubbling) to reach a totox of 24 which is at the upper limit of the GOED standard.…”
Section: Methodsmentioning
confidence: 99%